Bioinspired Precision Peeling of Ultrathin Bamboo Green Cellulose Frameworks for Light Management in Optoelectronics - Wang, Yan; Zhang, Yuan; Zuo, Yingfeng; Zhao, Dawei; Wu, Yiqiang (Nano-Micro Letters, 2025)
Cellulose frameworks have emerged as promising materials for light management due to their exceptional light-scattering capabilities and sustainable nature. Conventional biomass-derived cellulose frameworks face a fundamental trade-off between haze and transparency, coupled with impractical thicknesses (≥ 1 mm). Inspired by squid’s skin-peeling mechanism, this work develops a peroxyformic acid (HCOOOH)-enabled precision peeling strategy to isolate intact 10-µm-thick bamboo green (BG) frameworks—100 × thinner than wood-based counterparts while achieving an unprecedented optical performance (88% haze with 80% transparency). This performance surpasses delignified biomass (transparency < 40% at 1 mm) and matches engineered cellulose composites, yet requires no energy-intensive nanofibrillation. The preserved native cellulose I crystalline structure (64.76% crystallinity) and wax-coated uniaxial fibril alignment (Hermans factor: 0.23) contribute to high mechanical strength (903 MPa modulus) and broadband light scattering. As a light-management layer in polycrystalline silicon solar cells, the BG framework boosts photoelectric conversion efficiency by 0.41% absolute (18.74% → 19.15%), outperforming synthetic anti-reflective coatings. The work establishes a scalable, waste-to-wealth route for optical-grade cellulose materials in next-generation optoelectronics. Highlights: 1 First successful peeling of bamboo green into micrometer-scale optical films (10 μm) via a bioinspired peroxyformic acid strategy, achieving intact preservation of monolayer cellular structure. 2 Scalable and stable peeling process enables high-yield production of bamboo green frameworks, demonstrating significant potential for sustainable optical material applications. 3 Experimental validation in light management shows 0.41% absolute photoelectric conversion efficiency enhancement in solar cells, proving practical value as high-performance optical films.